Laser interstitial thermotherapy application for breast surgery: Current situation and new trends. (June 2017) - Kerbage, Yohan; Betrouni, Nacim; Collinet, Pierre; Azaïs, Henri; Mordon, Serge; Dewalle-Vignion, Anne-Sophie; Merlot, Benjamin
Abstract: While breast specialists debate on therapeutic de-escalation in breast cancer, the treatment of benign lesions is also discussed in relation to new percutaneous ablation techniques. The purpose of these innovations is to minimize potential morbidity. Laser Interstitial ThermoTherapy (LITT) is an option for the ablation of targeted nodules. This review evaluated the scientific publications investigating the LITT approach in malignant and benign breast disease. Three preclinical studies and eight clinical studies (2 studies including fibroadenomas and 6 studies including breast cancers) were reviewed. Although the feasibility and safety of LITT have been confirmed in a phase I trial, heterogeneous inclusion criteria and methods seem to be the main reason for LITT not being yet an extensively used treatment option. In conclusion, further development is necessary before this technique can be used in daily practice. Highlights: Laser interstitial therapy is a promising minimally invasive breast cancer treatment. Lack of damages prediction and uncertain guiding modalities are currently the main limits. Changes in immunocompetent cells after interstitial laser thermotherapy is an important concept to develop this technique.